Experimental study and application of similar materials in thick coal seam mining - Liu, Wei; Yin, Shangxian; Thanh, Hung Vo; Soltanian, Mohamad Reza; Yu, Qingyang; Lian, Huiqing; Yang, Songlin; Li, Yarui; Dai, Zhenxue (Frontiers in Energy Research, 2024)
The orthogonal experiments of similar materials were optimized and analyzed in order to accurately simulate the mechanical properties and the fracture evolution law of thick coal seam overlying strata during mining in this study. The experimental results indicated that similar materials using gypsum and calcium carbonate as cementing agents had a wide range of compressive strength (173.80 kPa–425.95 kPa) and were suitable for simulating various rock properties. Adding an appropriate amount of calcium carbonate can improve the brittleness and mechanical properties of similar materials using gypsum as cementing agents. The failure mode of similar materials transitioned from shear to tensile failure with the increase of the mass ratio of aggregate to cementing agents and the mass ratio of calcium carbonate to gypsum. Moreover, the compressive strength of similar materials rapidly decreased with an increase in the mass ratio of aggregate to cementing materials. And the compressive strength showed an increasing trend with the decrease of the mass ratio of calcium carbonate to gypsum. Moisture content had a significant impact on the density of similar materials, other parameters had small impacts. A thick coal seam mining experimental model was designed based on the experimental results of similar materials, which showed that Qianjiaying Mine may experience basic roof collapse when mining reached 58.1 m. The recommended periodic weighting pace for face pressure on the working face was approximately 15.0 m. Appropriate measures are necessary to adopt to prevent disasters after mining to a length of 58.1 m, followed by every 15.0 m of mining.